Difficulty in the Clinical Diagnosis of Tularemia: Highlighting the Importance of a Physical Exam - Rupin Kumar; Mohamed Mansour; Jacqueline Brunetto; Renuka Verma; Margaret Fisher; Jonathan Teitelbaum (Case Reports in Pediatrics)
We report an 18-month-old male who presented with fever and nonspecific symptoms. He was evaluated for multiple differential diagnoses including Kawasaki disease and JIA and received treatment for them. After he was readmitted, tularemia was considered based on the physical exam finding of an ulcer on the scalp and enlarged lymph nodes. Tularemia titers were positive, and the patient was given the appropriate antibiotic and was discharged home. Follow-up of the patient showed complete resolution of symptoms. This is a case that demonstrates the importance of physical exam in identifying rare diseases presenting with common signs and symptoms.